Implementation of Islamic religious education curriculum based on religious values in junior high schools - Salma Rafidah; Istanto Istanto (Inovasi Kurikulum, 2025)
Islamic Religious Education (Pendidikan Agama Islam or PAI) in secondary schools has a strategic role in shaping students' character in accordance with Islamic values. However, the implementation of the ideal PAI curriculum still faces several challenges, including differences in the perception of implementers, limited resources, and the influence of the social environment. The purpose of this article is to comprehensively analyze the implementation of PAI curriculum design in secondary education practice and how religious values can be integrated into all aspects of learning. Through the literature review method and qualitative analysis, this article finds that the role of teachers, school support, and family and community involvement have a significant impact on the success of curriculum implementation. In addition, Islamic values are reinforced not only through teaching materials, but also through role models and school culture. This paper can serve as a reference for policy makers, educators, and researchers in an effort to improve the relevance and effectiveness of PAI curriculum implementation at the secondary level. Improving the quality of curriculum implementation will contribute positively to the development of a young generation with character and faith.   Abstrak Pendidikan Agama Islam (PAI) di sekolah menengah memiliki peran strategis dalam membentuk karakter peserta didik sesuai dengan nilai-nilai Islam. Namun implementasi kurikulum PAI yang ideal masih menghadapi beberapa tantangan, diantaranya perbedaan persepsi pelaksana, keterbatasan sumber daya, dan pengaruh lingkungan sosial. Tujuan artikel ini untuk menganalisis secara komprehensif implementasi desain kurikulum PAI dalam praktik pendidikan menengah dan bagaimana nilai-nilai religius dapat diintegrasikan ke dalam semua aspek pembelajaran. Melalui metode tinjauan literatur dan analisis kualitatif artikel ini menemukan bahwa peran guru, dukungan sekolah, serta keterlibatan keluarga dan masyarakat memiliki dampak yang signifikan terhadap keberhasilan implementasi kurikulum. Selain itu, nilai-nilai Islam diperkuat tidak hanya melalui bahan ajar, tetapi juga melalui keteladanan dan budaya di sekolah. Tulisan ini dapat menjadi referensi bagi para pengambil kebijakan, pendidik dan peneliti dalam upaya meningkatkan relevansi dan efektivitas implementasi kurikulum PAI di tingkat menengah. Peningkatan kualitas implementasi kurikulum akan memberikan kontribusi positif bagi pengembangan generasi muda yang berkarakter dan beriman. Kata Kunci: implementasi kurikulum; nilai-nilai religius; pendidikan agama Islam; sekolah menengah pertama